2021
DOI: 10.1038/s41467-021-21456-1
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase Nedd4l promotes antiviral innate immunity by catalyzing K29-linked cysteine ubiquitination of TRAF3

Abstract: Ubiquitination is one of the most prevalent protein posttranslational modifications. Here, we show that E3 ligase Nedd4l positively regulates antiviral immunity by catalyzing K29-linked cysteine ubiquitination of TRAF3. Deficiency of Nedd4l significantly impairs type I interferon and proinflammatory cytokine production induced by virus infection both in vitro and in vivo. Nedd4l deficiency inhibits virus-induced ubiquitination of TRAF3, the binding between TRAF3 and TBK1, and subsequent phosphorylation of TBK1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…To further explore the mechanism by which ST inhibits caspase-11, we aimed to identify the protein responsible for regulating caspase-11 ubiquitination. In innate immunity, Nedd4l catalyzes the K29-linked ubiquitination of cysteine residues in TNF receptor-associated factor 3, which is key to innate antiviral immunity (Gao et al, 2021). Recent research found that Nedd4 is an important negative regulatory component of the non-canonical inflammasome pathway and that it directly interacts with caspase-11 and mediates the polyubiquitination of K48-linked caspase-11 at multiple K residues and subsequent degradation by the 26S proteasome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the mechanism by which ST inhibits caspase-11, we aimed to identify the protein responsible for regulating caspase-11 ubiquitination. In innate immunity, Nedd4l catalyzes the K29-linked ubiquitination of cysteine residues in TNF receptor-associated factor 3, which is key to innate antiviral immunity (Gao et al, 2021). Recent research found that Nedd4 is an important negative regulatory component of the non-canonical inflammasome pathway and that it directly interacts with caspase-11 and mediates the polyubiquitination of K48-linked caspase-11 at multiple K residues and subsequent degradation by the 26S proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Nedd4 is well known to play an important role in development and physiological growth (Cao et al, 2008). Moreover, Nedd4 regulates immune cell functions and plays important regulatory roles in adaptive immunity (Liu et al, 2017;Gao et al, 2021). In natural immunity, Nedd4 has an inhibitory effect on non-classical inflammasomes.…”
Section: Introductionmentioning
confidence: 99%
“…The original and most familiar function of NEDD4L is to regulate the epithelial Na + channel (ENaC), which is closely related to the fluctuation of blood pressure (23). In addition, NEDD4L also participates in DNA repair, antiviral immunity and tumor development (24)(25)(26). To date, multiple reports have shown that the expression of NEDD4L in cancers is abnormal, and various proteins have been validated to bind with NEDD4L or be ubiquitinated by NEDD4L, thus modulating the cancer development (27).…”
Section: Structure and Function Of Nedd4lmentioning
confidence: 99%
“…It is also understood that the E3 ubiquitin ligases HACE1 ( Mao et al, 2016 ), MID1 ( Chen et al, 2021 ), NEDD4L ( Gao et al, 2021 ), PRKN ( Sliter et al, 2018 ), RNF125 ( Arimoto et al, 2007 ), RNF170 ( Song et al, 2020 ), RNF216 ( Nakhaei et al, 2009 ), STUB1 ( Zhou et al, 2018 ), as well as UBE3A ( Furumai et al, 2019 ) are involved in antiviral innate defense and the generation of type I interferon (IFN) responses ( Figure 2 ). Again, besides NEDD4L, all these genes encode ligases involved in type I IFN negative feedback loops and, as such any dysfunction, would lead to uncontrolled type I IFN responses.…”
Section: Ndd-associated E3 Ubiquitin Ligases and Their Roles In The Immune Responsementioning
confidence: 99%